Healthcare costs according to obesity and physical activity: 8-year longitudinal study among patients assisted by the Brazilian National Healthcare System - de Morais, Luana Carolina [UNESP]; Araujo, Monique Yndawe Castanho [UNESP]; Koyama, Kelly Akemi Kikuti [UNESP]; Lemes, Ítalo Ribeiro [UNESP]; Fernandes, Romulo Araújo [UNESP]; Turi-Lynch, Bruna Camilo; Monteiro, Henrique Luiz [UNESP]; Codogno, Jamile Sanches [UNESP] (Elsevier, 2025)
INTRODUCTION: Obesity is a risk factor for the development of many chronic diseases, and, consequently, it is associated with an increase in the use of health services. On the other hand, practicing physical activity reduces healthcare costs. However, the long-term roles of physical activity and obesity in healthcare costs are not well explored in the literature. OBJECTIVE: This study aimed to investigate the physical activity (PA) and obesity trajectory in relation to health costs, in participants treated by primary care, over a period of eight years. METHODS: The sample included 291 participants, aged ≥ 50 years, evaluated between 2010 and 2018. Weight and height were used to calculate the body mass index (BMI), and PA was evaluated by a questionnaire. Healthcare costs were extracted from medical records. The General Structural Equation Model (GSEM) was used to analyze the trajectory of the variables in the eight-year follow-up. RESULTS: In 2010, the median healthcare cost was US$51.61, an increase of 54 % compared to 2018. BMI and PA decreased by around 2 % and 22.6 %, respectively. At baseline, BMI affected the trajectory of health costs, increasing costs by US$ 1.55 (p = 0.024). CONCLUSION: In conclusion, in eight years, participants presented decreases in BMI and PA and increases in health costs. BMI, but not PA, affected the increase in healthcare costs at baseline.